Construction of layer‐by‐layer assembled green coating on titanate nanotubes to improve the flame retardancy of epoxy resin. Issue 44 (16th May 2020) - Pan, Haifeng; Ma, Wenbin; Zhang, Zinan; Liu, Yifan; Lu, Fuqiang; Yu, Bihao
Abstract: In this study, phosphorus‐modified titania nanotubes (CH/PT‐TNTs) were obtained through the layer‐by‐layer assembly using titanium dioxide nanotubes (TNTs), Chitosan (CH) and synthetic phosphatized chitin (PT). Subsequently, CH/PT‐TNTs were incorporated into epoxy resin (EP) to improve the fire safety of epoxy resin. The results of TEM, FTIR, and XPS demonstrated that CH/PT coating was successfully constructed on the surface of TNTs. According to the results of Cone, the addition of CH/PT‐TNTs induced a significant improvement on the flame retardancy of EP, with only 2 wt% addition resulted in a remarkable reduction of peak heat release rate (48.8%) and total heat release (42.1%) compared to the pure EP, which is superior to TNTs at the same amount of addition. Moreover, the results of Raman spectroscopy indicated that the CH/PT coating helps to increase the degree of graphitization of the carbon layer. A possible flame‐retardant mechanism has been speculated on the synergistic effect between the CH/PT coating and the TNTs. Therefore, it is an effective method to improve the fire safety of epoxy resin, which provides a new idea for developing new environmentally friendly flame‐retardant epoxy resins. Abstract :